THE QUALITY OF LIFE OF THE WORKERS OF THE ELECTROLYSIS ALUMINIUM PRODUCTION WITH OCCUPATIONAL BRONCHO-PULMONARY PATHOLOGY - E. A. Abramatets (Scientific Сentre for Family Health and Human Reproduction Problems, 2013)
The impact of industrial aerosols (fluoride, aluminum oxide dust, coal tar distillates, aromatic and heterocyclic compounds) causes development of broncho-pulmonary pathology in professional workers. The aim of the work was to study the basic indicators of the quality of life and degree of influence of broncho-pulmonary pathology on the health status of patients with diagnosed occupational disease of respiratory system. 38 former employees of the basic professions of electrolysis aluminum production were divided into 2 groups. The first group consisted of 22 persons with FEV1 (forced expiratory volume in 1 second) of 70-80 % of the proper values, the second group included 16 people with fEV1 of 50-69 % of proper values. On the basis of the results of the COPD assessment test the patients of the first group marked moderate (18 %), strong (36 %) and extremely strong (46 %) impact of the disease on their lives. In the second group strong (37 %) and extremely strong (63 %) impact of the disease on patients' lives was registered. Total index of physical component of health in the first group was 37,3 ± 3,5 points, in the second group - 28,9 ± 2,3 points. The results of total index of mental component of health didn't differ significantly in both groups and were 44,1 ± 3,7 and 42,8 ± 2,8 points respectively. It was found that occupational respiratory diseases had negative influence both on summary mental component of health which characterized vitality, social and role functioning and mental health and also on total physical component of health which characterized physical and role functioning and patients' health. In this case lower values of total physical component of health were revealed in patients with moderate disorders of respiratory function in comparison with examined patients with slight decline in FEV1. Thus occupational diseases of respiratory system have negative impact on quality of life of patients and especially on their physical status. The degree of negative impact of the disease on patients' quality of life is determined by the severity of the disease. Functional indicators of respiratory function don't always correlate with subjective evaluation of health status by the patient.